UNDEVELOPED PREGNANCY:AN ASSESSMENT OF RISK FACTORS AND PROGNOSIS - Salokhova, D.K.; Atakhodzhaeva, F.A. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
The article gives the review of native and foreign literature on the problem of non-developing pregnancy. There have been singled out the main factors which lead to the development of non-developing pregnancy (life style, infections, hyperprolactinemia, adrenogenital syndromes). The role of immune and endocrine systems in the formation of non-developing pregnancy has been described. The prognostic criteria have been singled out, the principles of pre-conceptional preparation and prolongation of pregnancy during the repeated pregnancy planning have been described